A Conceptual Framework of Capacity Building in Training Contexts - Athirah Shahira’a, Abdullah; Shaik Azahar, Shaik Hussain (UCYP University, 2022)
This study focuses on creating a conceptual framework for capacity building, which is believed to be the same as training. The role of capacity building can be applied to individual, organizational and environmental aspects. However, this study only focuses on individuals involved in capacity-building activities. This capacity building can be widely used in empowering values, abilities, and expertise in various fields. There are two variables found in this study that have been stated. In addition, this study will look at how the development of this capacity affects individuals in training. In conclusion, the researcher has released a new conceptual framework produced from the philosophy of previous researchers.